Ecologie et cartographie des coraux d’eau froide du canyon de Lacaze-Duthiers en Méditerranée; Données de la campagne CALADU 2019 - Sanchez, Pierre; Fabri, Marie-claire (2020)
This work aimed to study populations of cold-water corals in the Lacaze-Duthiers canyon, a French canyon in the western part of the Gulf of Lion. the study was carried out using photos and videos of the wire-Remote Operated Vehicle: the HROV Ariane. Analysis of photos and videos allowed us to obtain information on the general biodiversity, on the spatial and vertical distribution and on the population density of the coldwater coral communities of the canyon but also on the size ranges and of colors of these species. Thus, it was noted that Madrepora oculata was the most represented species. This species has been observed in abundance ten times greater than the Lophelia pertusa species, which presented very dense distributions in places and then almost nothing in others (in patches). The highest densities of these two species were found in the same places but the maximum densities of M. oculata (7.6 / m2) were higher than those of L. pertusa (4.5 / m2). For the latter, it was mainly "Medium" size colonies while for M. oculata it was mainly "Small" size indicating strong recruitment. Colonies of L. pertusa were observed to be significantly deeper than those of M. oculata and D. cornigera. Finally, this video analysis also allowed us to highlight the strong presence of fishing waste in the canyon. Ce travail visait à étudier les populations de coraux d’eau froide dans le canyon de Lacaze-Duthiers, un canyon Français de la partie Ouest du Golfe du Lion. l’étude à été réalisée à partir de photos et vidéos du robot sous-marin filoguidé: le HROV Ariane. L’analyse de ces photos et vidéos a permis d’obtenir des informations sur la biodiversité générale, sur la distribution spatiale et verticale et sur la densité de population des communautés de coraux d’eau froide du canyon mais aussi sur les gammes de tailles et de couleurs de ces espèces. Ainsi, on a pu noter que Madrepora oculata était l’espèce la plus représentée. Cette espèce à été observée en abondance dix foix suppérieure à l’espèce Lophelia pertusa qui elle ...